New records of Digitaria filiformis var. laeviglumis (Paniceae, Panicoideae, Poaceae) for the Flora del Bajío and Durango, Mexico - Sánchez Ken, Jorge Gabriel (Instituto de Ecología, A.C., 2019)
Background and Aims: Since its publication in 1920, Digitaria filiformis var. laeviglumis had been considered as an endangered taxon endemic to New Hampshire, USA. However, a recent inventory of the grasses of Mexico showed that it also occurs outside its type locality. New findings for the ongoing project Flora del Bajío have yielded additional new records. The objective of this work is to report this taxon from the Mexican states of Michoacán and Durango, increasing the number of known localities of Digitaria filiformis var. laeviglumis.Methods: Online databases and herbaria were reviewed. Botanical herbarium specimens were collected in the state of Michoacán.Key results: Digitaria filiformis var. laeviglumis is reported as new for the Flora del Bajío in the state of Michoacán, as well as from a herbarium specimen from Durango which has both var. laeviglumis and var. filiformis mounted on the same sheet and that was misplaced among other specimens.Conclusions: With the addition of this variety, the number of taxa in the subfamily Panicoideae increases for the Flora del Bajío and the state Durango. With these findings there are more intermediate localities between the northern and southern range for this variety.